2005
DOI: 10.1007/bf02977406
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of cannabidiol, cannabinol, and \gD9-tetrahydrocannabinol in human hair by gas chromatography-mass spectrometryin human hair by gas chromatography-mass spectrometry

Abstract: An analytical method was developed for evaluating the cannabidiol (CBD), cannabinol (CBN), and delta9-tetrahydrocannabinol (delta9-THC) level in human hair using gas chromatography-mass spectrometry (GC-MS). Hair samples (50 mg) were washed with isopropyl alcohol and cut into small fragments (< 1 mm). After adding a deuterated internal standard, the hair samples were incubated in 1.0 M NaOH for 10 min at 95 degrees C. The analytes from the resulting hydrolyzed samples were extracted using a mixture of n-hexane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 13 publications
1
29
0
Order By: Relevance
“…The identification of the main THC metabolite 11-nor-D-9-tetrahydrocannabinol-9-carboxylic acid (THC-COOH) in hair, would certainly document active cannabis use more effectively than the detection of the parent drug or other cannabinoids such as CBD and CBN, which might come from environmental exposure [8,[25][26][27]. Nevertheless, this metabolite has much lower affinity for hair matrix (even compared with other cannabinoids) and, generally, is found only in pg/mg range.…”
Section: Lod and Loqmentioning
confidence: 99%
See 1 more Smart Citation
“…The identification of the main THC metabolite 11-nor-D-9-tetrahydrocannabinol-9-carboxylic acid (THC-COOH) in hair, would certainly document active cannabis use more effectively than the detection of the parent drug or other cannabinoids such as CBD and CBN, which might come from environmental exposure [8,[25][26][27]. Nevertheless, this metabolite has much lower affinity for hair matrix (even compared with other cannabinoids) and, generally, is found only in pg/mg range.…”
Section: Lod and Loqmentioning
confidence: 99%
“…Some methods have been described in the scientific literature for the determination of cannabinoids in hair samples. GC-MS is the technique of choice in the majority of these methods [3,[7][8][9][10][11]. Highest sensitivity was reached by the use of MS/MS [3,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Various cannabinoids have been analyzed in plasma, blood and urine [1][2][3], but their detection in the more esoteric matrices such as sweat, oral fluid and hair has only recently been addressed. Kim et al [4] report an analytical method for the detection of CBN, CBD and THC in hair, with a detection limit of 6 pg/mg for THC. Other authors have analyzed cannabinoids in hair, using various techniques, such as solid-phase micro-extraction [5] and two-dimensional chromatography [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, as mentioned above, these detectors are commonly not used in routine analyses of forensic samples. Among PFPA and PFPOH, acylation reagents such as trifluoroacetic anhydride (TFAA) and N-methyl-bis(trifluoroacetamide) (MBTFA) are also used for analysis of cannabinoids in human materials [111][112][113][114]. Trideuterated THC-COOH (7.4) is the most commonly used internal standard for the analysis of metabolites with GC-MS. Baptista et al [103] have shown that the limit of quantification (LOQ) for the important metabolite THC-COOH is much more better if negative chemical ionization (NCI) is used instead of electron ionization (EI).…”
Section: Gas Chromatographic Methods (Gc)mentioning
confidence: 99%